Fiduciary Systems Assessment : Maharashtra Rural Water Supply and Sanitation Program - World Bank (Washington, DC, 2014)
A fiduciary systems assessment (FSA) was carried out to evaluate the arrangements relevant to the program and to determine whether they provide reasonable assurance that the program funds will be used for their intended purpose. Taking into account the improvements required and the agreement on the actions required to strengthen the systems (which are reflected in the program action plan (PAP), the overall fiduciary framework is considered adequate to support program management and to achieve desired results. Government of Maharashtra (GoM) has a well-developed budgetary framework that ensures allocation of adequate resources to all departments and programs. There is sufficient predictability in the availability of resources; however, to maintain transparency in GoM's financing, an exclusive budget line has been allocated to this program as is usually done by GoM for externally aided projects. Fiduciary arrangements in the sector are guided by several rules and legislations, including the state financial rules, public works department (PWD) manual, store purchase rules, Maharashtra jeevan pradhikaran (MJP) act, Zila Parishad (ZP) account code and the Bombay panchayat rules. The existing governance and accountability arrangements in water supply and sanitation department (WSSD) include the anti-corruption bureau, which enforces the prevention of corruption act, 1988; audits by the comptroller and auditor general (C and AG) of India, the country's premier auditor; right to information (RTI) act 2005; and WSSD's vigilance function and its grievance redress system (E-Pani).